Iron aluminate cement and preparation method thereof

By using early strength admixtures and composite latex powder in ferroaluminate cement, the problem of insufficient cement strength and rheological performance in the prior art is solved, and the effects of high strength, good rheology and excellent processing performance are achieved. Promote the reuse of resources.

CN119430703APending Publication Date: 2025-02-14GUANGXI YUNYAN SPECIAL CEMENT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411895047.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-21
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, the preparation of ferroalaluminate cement doped with organic water reducers cannot significantly improve the cement strength, and cannot improve rheology and processing performance while ensuring high strength of cement.

Method used

Using premature strength admixture and composite latex powder, premature strength admixture is prepared through neutralization reaction to form a long-chain water reducing agent, and react with calcium lignin sulfonate and triethanolamine to form a monomer with retarding and water reducing effects. Modification; composite latex powder is prepared by spray-drying of core-shell polymer emulsion, with good chemical corrosion resistance and flexibility.

Benefits of technology

The strength and rheological properties of ferroalaluminate cement are significantly improved, the processing performance of cement is improved, and the effective utilization of waste resources is achieved by reusing red mud resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses aluminoferrite cement and a preparation method thereof, belongs to the technical field of building materials, and aims to solve the technical problems that in the prior art, the strength of the cement cannot be remarkably improved by doping an organic water reducing agent into the aluminoferrite cement, and the rheological property and the processability cannot be improved on the premise of ensuring the high strength of the cement. The iron aluminate cement comprises iron aluminate clinker, red mud, an early strength admixture and composite latex powder. According to the early strength admixture, sodium aminobenzene sulfonate, formaldehyde and cetylnaphthalene react to prepare a long-chain water reducing agent; the water reducing agent is modified by calcium lignosulphonate and triethanolamine to obtain the early strength admixture. The preparation method comprises the following steps: coating a nanoscale inorganic filler with a core-shell polymer emulsion containing an inner-layer structure and an outer-layer structure, and carrying out spray drying to obtain the composite latex powder. The prepared aluminoferrite cement has the advantages of high strength, high water reducing effect, high hydration speed and good rheological property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to ferroaluminate cement and a preparation method thereof. Background Art

[0002] Cement is widely used in building materials due to its good gelling properties; it can harden in water and harden in the air to produce strength. With the continuous improvement of cement production technology, cement varieties are also constantly innovating, and the performance is constantly improving. Ferroaluminate cement (high iron sulfoaluminate cement) is a type of sulfoaluminate cement. Sulphoaluminate cement is superior to silicate cement because of its fast setting and low negative hardening temperature. It is often used for emergency repairs of bridge decks and municipal roads in winter construction; however, how to ensure that ferroaluminate cement has a faster hydration speed and strength while still having excellent rheological properties and processing properties is a technical problem that needs to be solved.

[0003] Patent application CN115448681A discloses a kind of ferroaluminate cement for repair and its preparation method. The raw materials of ferroaluminate cement clinker, silica fume, gypsum, water reducer, nitrite, reinforcing agent and calcium oxide are combined to quickly generate a certain proportion of Al, calcium sulfonate, iron gel, aluminum gel and CSH gel; the polyphosphate water reducer used can chelate with the metal ions in seawater, so as to ensure the strength increase of the hydration product in the later erosion environment. However, in non-marine environment, the above-mentioned polyphosphate water reducer cannot improve the ultra-early strength of cement paste. In addition, on the premise of ensuring that the cement has high mechanical strength, it is also a technical problem that needs to be solved urgently to make it have excellent processing performance.

[0004] In addition, the cement industry is facing problems such as natural resource depletion, increased energy supply costs, and increased requirements for carbon dioxide emission reduction. Therefore, it is necessary to replace cement raw materials with eco-friendly materials to reduce the adverse effects of cement production on the environment.

[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0006] The object of the present invention is to provide an aluminoaluminate cement and a preparation method thereof, so as to solve the technical problems that the aluminoaluminate cement prepared by adding an organic water reducer in the prior art cannot significantly improve the strength of the cement, and cannot improve the rheology and processing performance under the premise of ensuring the high strength of the cement.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A ferroaluminate cement comprises, by weight, 75-85 parts of ferroaluminate clinker, 5-10 parts of red mud, 3-5 parts of early strength admixture and 5-10 parts of composite latex powder.

[0009] Furthermore, the preparation method of the early strength admixture comprises the following steps:

[0010] A1, an organic solvent and sodium aminobenzenesulfonate are mixed, and then a 30-35%wt formaldehyde aqueous solution is added dropwise, and the addition is completed within 1-2 hours; after the addition is completed, a reaction system is obtained; the reaction system is placed in a closed environment, and reacted at 90-95°C for 3-4 hours to obtain an intermediate; then hexadecylnaphthalene and 98%wt concentrated sulfuric acid are added to the intermediate, the temperature is raised to 110-120°C, and the reaction is carried out at this temperature for 2-3 hours to obtain a long-chain water reducer.

[0011] The reaction formula for preparing long-chain water reducer by reacting sodium aminobenzenesulfonate, formaldehyde and hexadecylnaphthalene is as follows:

[0012]

[0013] A2. Heat water to 80-90°C, mix calcium lignin sulfonate, anhydrous sodium sulfate, triethanolamine, long-chain water reducer and 30%wt sodium hydroxide solution with water, stir evenly to obtain a reactant; heat the reactant to 95-105°C, keep the temperature at this temperature for 2-3 days to obtain an early strength admixture.

[0014] Calcium lignin sulfonate and triethanolamine both contain polyhydroxyl functional groups and can undergo neutralization reaction with long-chain water reducers, thereby preparing an early strength admixture modified with a multifunctional monomer.

[0015] Furthermore, in step A1, the preparation method of the organic solvent is: mixing ethanol and water in a mass ratio of 2-3:1 to obtain a solution; then adding 0.1 mol / L NaOH solution to the solution, adjusting the pH value of the solution to 8-9, and obtaining an organic solvent; the amount ratio of the organic solvent, sodium aminobenzenesulfonate and formaldehyde aqueous solution is 50mL:20-30g:50-60mL; the amount ratio of hexadecylnaphthalene and concentrated sulfuric acid is 10-15g:3-5mL.

[0016] Furthermore, in step A2, the usage ratio of calcium lignin sulfonate, anhydrous sodium sulfate, triethanolamine, long-chain water reducer, sodium hydroxide solution and water is 3.5-5g:10-15g:0.5-0.8g:5-10g:3-5g:60-65g.

[0017] Furthermore, the preparation method of the composite latex powder comprises the following steps:

[0018] B1, deionized water, eugenol epoxy resin, N-hydroxyacrylamide and styrene are mixed uniformly to obtain a monomer mixture A; a chain transfer agent and an emulsifier A are added to the monomer mixture A, stirred and dissolved to obtain a core pre-emulsion;

[0019] The core pre-emulsion was prepared by using eugenol epoxy resin, N-hydroxyacrylamide and styrene as reaction monomers and adding a proper amount of emulsifier.

[0020] B2, deionized water, tert-butyl vinyl carbonate and eugenol epoxy resin are mixed uniformly to obtain a monomer mixture B; emulsifier B is added to the monomer mixture B, and the mixture is mixed and stirred uniformly to obtain a shell pre-emulsion;

[0021] The shell pre-emulsion was prepared by using versatate vinyl carbonate and eugenol epoxy resin as reaction monomers and adding a proper amount of emulsifier.

[0022] B3, heating deionized water, ammonium persulfate and part of the core pre-emulsion to 75-80°C, reacting for 15-20 minutes, to obtain an auxiliary agent solution; adding the remaining core pre-emulsion and initiator solution A dropwise to the auxiliary agent solution at the same time, adding the core pre-emulsion within 1 hour, adding the initiator solution within 1.5 hours, and keeping the temperature for 0.5-1 hour after the addition is completed, to obtain a core copolymer;

[0023] Under the action of the initiator, the core pre-emulsion undergoes self-polymerization to obtain a core copolymer.

[0024] Eugenol epoxy resin, N-hydroxyacrylamide and styrene react to obtain a core copolymer as follows:

[0025]

[0026] B4, adding the shell pre-emulsion and the initiator solution dropwise to the core copolymer at the same time, adding the shell pre-emulsion within 2 hours, and adding the initiator solution within 2.5 hours. After the addition is completed, keep warm for 1-1.5 hours, then cool to 30-40° C., filter, and discharge to obtain a core-shell polymer emulsion;

[0027] Then, the shell pre-emulsion is continuously added to the core copolymer. Under the action of the initiator, the shell pre-emulsion undergoes addition polymerization reaction on the outer layer of the core copolymer to prepare a core-shell polymer emulsion containing inner and outer layer structures.

[0028] The reaction formula of versatate vinyl ester and eugenol epoxy resin is as follows:

[0029]

[0030] B5. Add the core-shell polymer emulsion and the nano-scale inorganic filler into a spray dryer for spray drying to prepare a composite latex powder.

[0031] After being spray-dried, the core-shell polymer latex and the nanometer-scale inorganic filler are aggregated together to form spherical particles with a diameter increased by several dozen times, that is, the prepared composite latex powder with a core-shell structure.

[0032] Furthermore, in step B1, the chain transfer agent is dodecyl mercaptan, and the emulsifier A is sodium dodecyl diphenyl oxide disulfonate; the amount ratio of the deionized water, eugenol epoxy resin, N-hydroxyacrylamide and styrene, the chain transfer agent and the emulsifier A is 100mL:30-40g:15-20g:50-100g:4-5g:5-10g.

[0033] Furthermore, in step B2, the emulsifier B is sodium dodecyl diphenyl oxide disulfonate; the amount ratio of the deionized water, tert-butyl vinyl carbonate, eugenol epoxy resin and emulsifier B is 200g:30-50g:20-30g:5-10g; in step B3, 3-5g of ammonium persulfate and 100g of deionized water are mixed to obtain an initiator solution; the amount ratio of deionized water, ammonium persulfate, part of the core pre-emulsion, the remaining core pre-emulsion and the initiator solution is 300g:0.5-1g:10g:190-200g:100g; in step B4, the amount ratio of the core copolymer, the shell pre-emulsion and the initiator solution is 300-400g:200-300g:100g.

[0034] Furthermore, in step B5, the nanoscale inorganic filler is obtained by adding natural zeolite into a grinder and grinding it to 50-100 nm; the mass ratio of the core-shell polymer emulsion to the nanoscale inorganic filler is 90-95:5-10; the inlet temperature of the spray dryer is 170-180°C, and the outlet temperature is 100°C.

[0035] As another aspect of the present invention, a method for preparing ferroaluminate cement comprises the following steps:

[0036] S1. Mixing aluminoferrate clinker, red mud, early strength admixture and composite latex powder to obtain a mixture; grinding the mixture to ensure that the residue after passing through an 80 μm sieve is no more than 10-15%wt, and the residue after passing through a 45 μm sieve is no more than 15-20%wt, to obtain a raw material;

[0037] S2. The raw materials are placed in a curing box at 20-22° C. and 90 RH% for curing and demolding to obtain demolded cement; the demolded cement is placed in a curing box at 20-22° C. and 65-70 RH% for curing for 28 days to obtain ferroaluminate cement.

[0038] The present invention has the following beneficial effects:

[0039] 1. The early strength admixture prepared by the present invention uses benzene ring as the main chain and skeleton, and the side chain is grafted with long fatty chains, so that the prepared early strength admixture can form a certain steric hindrance effect, thereby having a better dispersing effect on cement. The above-mentioned long-chain water reducer absorbs and grafts triethanolamine and calcium lignin sulfonate through a neutralization reaction, and finally obtains the early strength admixture. The polyhydroxyl groups of triethanolamine can form hydrogen bonds on the surface of cement, so that the prepared early strength admixture has a certain retarding effect; in addition, the addition of calcium lignin sulfonate makes the prepared early strength admixture have a water-reducing effect. The addition of the early strength admixture can enable the prepared aluminoferrocement to obtain higher strength in a shorter setting time; in addition, when preparing aluminoferrocement cement, a small amount of red mud is used to replace the iron phase of aluminoferrocement clinker to achieve the recycling of waste resources.

[0040] 2. The present invention adds an appropriate amount of composite latex powder to the prepared ferroaluminate cement. Eugenol epoxy resin, N-hydroxyacrylamide and styrene are used as monomers, and the core structure is prepared by addition polymerization; tert-butyl ester and eugenol epoxy resin are used as monomers, and the shell structure is prepared by addition polymerization. Tert-butyl ester has a high glass transition temperature and has a good internal plasticizing effect. As a monomer constituting the shell, it can provide good chemical corrosion resistance and flexibility for the prepared composite latex powder. The eugenol epoxy resin monomer used contains an active small molecule epoxy structure, which can react with N-hydroxyacrylamide to form a three-dimensional network cross-linked structure and a core-shell composite structure with inner and outer layers cross-linked. The core-shell polymer emulsion is spray-dried to aggregate from the initial 2-5μm to form spherical particles of 80-100μm; the spherical particles are coated with inorganic nanoparticles, thereby converting the dispersion into a fluid powder. The composite latex powder has a dual role; on the one hand, the redispersible latex powder can form a film on the cement surface to reduce the evaporation of water. On the other hand, the above-mentioned composite latex powder has good filling behavior, which can make the hardened cement structure dense, thereby improving the internal structure of cement, increasing the later strength of cement, and thus improving the flexural and compressive strength of cement. DETAILED DESCRIPTION

[0041] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] The eugenol epoxy resin in Examples 4-6 of the present invention is synthesized with reference to "Heterogeneous Catalytic Synthesis and Performance of Eugenol Silicone Epoxy Resin", and its epoxy equivalent is 0.420 mol / 100 g; the red mud in Examples 7-9 is purchased from Lingshou County Daye Mineral Products Processing Plant, with a product number of 1030 and a mesh size of 325-350 mesh; the ferroaluminate cement clinker in Examples 7-9 is purchased from Zhengzhou Kerui Refractory Materials Co., Ltd., and its composition includes FAC clinker and anhydrite, and the gypsum coefficient M=0.03-0.05.

[0043] Example 1

[0044] This embodiment provides a method for preparing an early strength admixture for ferroaluminate cement, comprising the following steps:

[0045] A1. Mix ethanol and water in a mass ratio of 2:1 to obtain a solution; add 0.1 mol / L NaOH solution to the solution, adjust the pH value of the solution to 8, and obtain an organic solvent. According to weight parts, add 50 mL of organic solvent to a 500 mL hydrothermal reactor, then add 20 g of sodium aminobenzenesulfonate to the hydrothermal reactor, and then add 50 mL, 30% wt formaldehyde aqueous solution to the hydrothermal reactor drop by drop, and control the addition to be completed within 1 hour; after the addition is completed, a reaction system is obtained. Then the hydrothermal reactor is closed, heated to 90 ° C, and reacted at this temperature for 3 hours to obtain an intermediate. Then 10 g of hexadecylnaphthalene and 5 mL, 98% wt concentrated sulfuric acid are added to the hydrothermal reactor, heated to 110 ° C, and reacted at this temperature for 2 hours to obtain a long-chain water reducer.

[0046] A2. Add 60g of water to a 500mL hydrothermal reactor, and then heat the hydrothermal reactor to 80°C. Then add 3.5g of calcium lignin sulfonate, 10g of anhydrous sodium sulfate, 0.5g of triethanolamine, 5g of long-chain water reducer, and 3g of 30%wt sodium hydroxide solution to the reactor, mix and stir evenly to obtain a reactant. Heat the hydrothermal reactor to 95°C, keep the reaction at this temperature for 2d, and prepare a reaction solution.

[0047] A3. The reaction solution was adjusted to pH 8 using 30%wt NaOH solution, and then filtered through a 100-mesh sieve to prepare an early strength admixture.

[0048] Example 2

[0049] This embodiment provides a method for preparing an early strength admixture for ferroaluminate cement, comprising the following steps:

[0050] A1. Mix ethanol and water in a mass ratio of 2.5:1 to obtain a solution; add 0.1 mol / L NaOH solution to the solution, adjust the pH value of the solution to 8.3, and obtain an organic solvent. According to weight parts, add 50 mL of organic solvent to a 500 mL hydrothermal reactor, then add 25 g of sodium aminobenzenesulfonate to the hydrothermal reactor, and then add 53 mL, 30% wt formaldehyde aqueous solution to the hydrothermal reactor drop by drop, and control the addition to be completed within 1 hour; after the addition is completed, a reaction system is obtained. Then the hydrothermal reactor is closed, heated to 92 ° C, and reacted at this temperature for 3.5 hours to obtain an intermediate. Then 12 g of hexadecylnaphthalene and 4 mL, 98% wt concentrated sulfuric acid are added to the hydrothermal reactor, heated to 115 ° C, and reacted at this temperature for 2.5 hours to obtain a long-chain water reducer.

[0051] A2. Add 62g of water to a 500mL hydrothermal reactor, and then heat the hydrothermal reactor to 88°C. Then add 4g of calcium lignin sulfonate, 12g of anhydrous sodium sulfate, 0.6g of triethanolamine, 8g of long-chain water reducer, and 4g of 30%wt sodium hydroxide solution to the reactor, mix and stir evenly to obtain a reactant. Then heat the hydrothermal reactor to 100°C, keep the reaction at this temperature for 2.5 days, and prepare a reaction solution.

[0052] A3. The reaction solution was adjusted to pH 8.8 using 30%wt NaOH solution, and then filtered through a 100-mesh sieve to prepare an early strength admixture.

[0053] Example 3

[0054] This embodiment provides a method for preparing an early strength admixture for ferroaluminate cement, comprising the following steps:

[0055] A1. Mix ethanol and water in a mass ratio of 3:1 to obtain a solution; add 0.1 mol / L NaOH solution to the solution, adjust the pH value of the solution to 9, and obtain an organic solvent. According to weight parts, add 50 mL of organic solvent to a 500 mL hydrothermal reactor, then add 30 g of sodium aminobenzenesulfonate to the hydrothermal reactor, and then add 60 mL, 30% wt formaldehyde aqueous solution to the hydrothermal reactor drop by drop, and control the addition to be completed within 2 hours; after the addition is completed, a reaction system is obtained. Then the hydrothermal reactor is closed, heated to 95 ° C, and reacted at this temperature for 4 hours to obtain an intermediate. Then 15 g of hexadecylnaphthalene and 5 mL, 98% wt concentrated sulfuric acid are added to the hydrothermal reactor, heated to 120 ° C, and reacted at this temperature for 3 hours to obtain a long-chain water reducer.

[0056] A2. Add 65g of water to a 500mL hydrothermal reactor, and then heat the hydrothermal reactor to 90°C. Then add 5g of calcium lignin sulfonate, 15g of anhydrous sodium sulfate, 0.8g of triethanolamine, 10g of long-chain water reducer, and 5g of 30%wt sodium hydroxide solution to the reactor, mix and stir evenly to obtain a reactant. Then heat the hydrothermal reactor to 105°C, keep the temperature at this temperature for 3d, and prepare a reaction solution.

[0057] A3. The reaction solution was adjusted to pH 9 with 30%wt NaOH solution, and then filtered through a 100-mesh sieve to prepare an early strength admixture.

[0058] Example 4

[0059] This embodiment provides a method for preparing a composite latex powder for ferroaluminate cement, comprising the following steps:

[0060] B1. Add 100 mL of deionized water into a 500 mL reactor, then add 30 g of eugenol epoxy resin, 15 g of N-hydroxyacrylamide and 100 g of styrene into the reactor, mix well, and obtain a monomer mixture A. Add 5 g of chain transfer agent dodecyl mercaptan and 10 g of emulsifier sodium dodecyl diphenyl ether disulfonate into the above monomer mixture A, stir and dissolve, and obtain a core pre-emulsion.

[0061] B2. 200 g of deionized water, 30 g of tert-butyl vinyl carbonate and 20 g of eugenol epoxy resin were mixed to obtain a monomer mixture B. 5 g of an emulsifier, sodium dodecyl diphenyl ether disulfonate, was added to the monomer mixture B, and the mixture was stirred to obtain a shell pre-emulsion.

[0062] B3. Mix 3g of ammonium persulfate and 100g of deionized water to obtain an initiator solution. According to weight, add 300g of deionized water, 0.5g of ammonium persulfate and 10g of core pre-emulsion to a hydrothermal reactor, heat to 75°C, react for 15min, and obtain an auxiliary agent solution. Add 190g of core pre-emulsion and 100g of initiator solution drop by drop to the above auxiliary agent solution at the same time, add the core pre-emulsion within 1h, and add the initiator solution within 1.5h. After the addition is completed, keep warm for 0.5h to obtain a core copolymer. Retain 300 g of the core copolymer in the hydrothermal reactor, then add 200 g of the shell pre-emulsion and 100 g of the initiator solution drop by drop into the hydrothermal reactor at the same time, add the shell pre-emulsion within 2 hours, and add the initiator solution within 2.5 hours. After the addition is completed, keep warm for 1 hour, then cool to 30°C, filter, and discharge to obtain a core-shell polymer emulsion.

[0063] B4. Add the core-shell polymer emulsion and the nano-scale inorganic filler in a mass ratio of 95:5 into a spray dryer for spray drying; wherein the inlet temperature of the spray dryer is 170° C. and the outlet temperature is 100° C., to prepare a composite latex powder.

[0064] Example 5

[0065] This embodiment provides a method for preparing a composite latex powder for ferroaluminate cement, comprising the following steps:

[0066] B1. Add 100 mL of deionized water into a 500 mL reactor, then add 35 g of eugenol epoxy resin, 18 g of N-hydroxyacrylamide and 80 g of styrene into the reactor, mix well, and obtain a monomer mixture A. Add 4.5 g of chain transfer agent dodecyl mercaptan and 8 g of emulsifier A sodium dodecyl diphenyl ether disulfonate into the above monomer mixture A, stir and dissolve, and obtain a core pre-emulsion.

[0067] B2. Mix 200 g of deionized water, 40 g of tert-butyl vinyl carbonate and 25 g of eugenol epoxy resin to obtain a monomer mixture B. Add 6 g of emulsifier B sodium dodecyl diphenyl ether disulfonate to the monomer mixture B, mix and stir to obtain a shell pre-emulsion.

[0068] B3. Mix 4g of ammonium persulfate and 100g of deionized water to obtain an initiator solution. According to weight, add 300g of deionized water, 0.8g of ammonium persulfate and 10g of core pre-emulsion to a hydrothermal reactor, heat to 76°C, react for 16min, and obtain an auxiliary solution. Add 195g of core pre-emulsion and 100g of initiator solution drop by drop to the above auxiliary solution at the same time, add the core pre-emulsion within 1h, and add 50mL of initiator solution within 1.5h. After the addition is completed, keep warm for 0.8h to obtain a core copolymer. Retain 350 g of the core copolymer in the hydrothermal reactor, then add 250 g of the shell pre-emulsion and 50 g of the initiator solution drop by drop into the hydrothermal reactor at the same time, add the shell pre-emulsion within 2 hours, and add the initiator solution within 2.5 hours. After the addition is completed, keep warm for 1.2 hours, then cool to 33°C, filter, and discharge to obtain a core-shell polymer emulsion.

[0069] B4. Add the core-shell polymer emulsion and the nano-scale inorganic filler in a mass ratio of 92:8 into a spray dryer for spray drying; wherein the inlet temperature of the spray dryer is 177° C. and the outlet temperature is 100° C., to prepare a composite latex powder.

[0070] Example 6

[0071] This embodiment provides a method for preparing a composite latex powder for ferroaluminate cement, comprising the following steps:

[0072] B1. Add 100 mL of deionized water into a 500 mL reactor, then add 40 g of eugenol epoxy resin, 20 g of N-hydroxyacrylamide and 50 g of styrene into the reactor, mix well, and obtain a monomer mixture A. Add 4 g of chain transfer agent dodecyl mercaptan and 5 g of emulsifier sodium dodecyl diphenyl ether disulfonate into the above monomer mixture A, stir and dissolve, and obtain a core pre-emulsion.

[0073] B2. 200 g of deionized water, 50 g of versatate and 30 g of eugenol epoxy resin were mixed to obtain a monomer mixture B. 10 g of an emulsifier, sodium dodecyl diphenyl ether disulfonate, was added to the monomer mixture B, and the mixture was stirred to obtain a shell pre-emulsion.

[0074] B3. Mix 5g of ammonium persulfate and 100g of deionized water to obtain an initiator solution. According to weight, add 300g of deionized water, 1g of ammonium persulfate and 10g of core pre-emulsion into a hydrothermal reactor, heat to 80°C, react for 20min, and obtain an auxiliary agent solution. Add 200g of core pre-emulsion and 100g of initiator solution drop by drop into the above auxiliary agent solution at the same time, add the core pre-emulsion within 1h, and add the initiator solution within 1.5h. After the addition is completed, keep warm for 1h to obtain a core copolymer. Retain 400 g of the core copolymer in the hydrothermal reactor, then add 300 g of the shell pre-emulsion and 100 g of the initiator solution drop by drop into the hydrothermal reactor at the same time, add the shell pre-emulsion within 2 hours, and add the initiator solution B within 2.5 hours. After the addition is completed, keep warm for 1.5 hours, then cool to 30°C, filter, and discharge to obtain a core-shell polymer emulsion.

[0075] B4. Add the core-shell polymer emulsion and the nano-scale inorganic filler in a mass ratio of 90:10 into a spray dryer for spray drying; wherein the inlet temperature of the spray dryer is 180° C. and the outlet temperature is 100° C., to prepare a composite latex powder.

[0076] Example 7

[0077] This embodiment provides a method for preparing ferroaluminate cement, comprising the following steps:

[0078] B1. According to parts by weight, 75 parts of aluminoferrite clinker (gypsum coefficient M=0.03), 5 parts of red mud, 3 parts of the early strength admixture prepared in Example 1 and 5 parts of the composite latex powder prepared in Example 4 were added to a blender and stirred evenly to obtain a mixture. The mixture was ground to meet the requirement that the residue after passing through an 80 μm sieve was no more than 10%wt, and the residue after passing through a 45 μm sieve was no more than 15%wt, to obtain a raw material.

[0079] B2. Pour the raw materials into the mold, place them in a curing box for curing for 24 hours, and then demould them. The temperature of the curing box is set to 20°C and the curing humidity is 90% to obtain the demoulded cement. The demoulded cement is placed in a curing box with a curing temperature of 20°C and a curing humidity of 65% for curing for 28 days to obtain ferroaluminate cement.

[0080] Example 8

[0081] This embodiment provides a method for preparing ferroaluminate cement, comprising the following steps:

[0082] B1. According to parts by weight, 75 parts of aluminoferrite clinker (gypsum coefficient M=0.05), 5 parts of red mud, 3 parts of the early strength admixture prepared in Example 2 and 5 parts of the composite latex powder prepared in Example 5 were added to a blender and stirred evenly to obtain a mixture. The mixture was ground to meet the requirement that the residue after passing through an 80 μm sieve was no more than 12%wt and the residue after passing through a 45 μm sieve was no more than 18%wt to obtain a raw material.

[0083] B2. Pour the raw materials into the mold, place them in a curing box for curing for 24 hours, and then demould them. The temperature of the curing box is set to 22°C and the curing humidity is 92% to obtain the demoulded cement. The demoulded cement is placed in a curing box with a curing temperature of 22°C and a curing humidity of 68% for curing for 28 days to obtain ferroaluminate cement.

[0084] Example 9

[0085] This embodiment provides a method for preparing ferroaluminate cement, comprising the following steps:

[0086] B1. According to weight parts, 85 parts of aluminoferrite clinker (gypsum coefficient M=0.05), 10 parts of red mud, 5 parts of early strength admixture prepared in Example 3 and 10 parts of composite latex powder prepared in Example 6 were added to a blender and stirred evenly to obtain a mixture. The mixture was ground to meet the requirement that the residue after passing through an 80 μm sieve was no more than 10%wt and the residue after passing through a 45 μm sieve was no more than 15%wt to obtain a raw material.

[0087] B2. Pour the raw materials into the mold, place them in a curing box for curing for 24 hours, and then demould them. The temperature of the curing box is set to 22°C and the curing humidity is 95% to obtain the demoulded cement. The demoulded cement is placed in a curing box with a curing temperature of 20°C and a curing humidity of 70% for curing for 28 days to obtain ferroaluminate cement.

[0088] Comparative Example 1

[0089] The difference between this comparative example and Example 9 is that when preparing the early strength admixture, hexadecylnaphthalene is replaced by 2-methylnaphthalene in the same amount of substance.

[0090] Comparative Example 2

[0091] The difference between this comparative example and Example 9 is that when preparing the early strength admixture, steps A2 and A3 are omitted, and the early strength admixture is replaced by a long-chain water reducer.

[0092] Comparative Example 3

[0093] The difference between this comparative example and Example 9 is that eugenol is used instead of eugenol epoxy resin when preparing the core pre-emulsion and the shell pre-emulsion.

[0094] Comparative Example 4

[0095] The difference between this comparative example and Example 9 is that when preparing the shell pre-emulsion, ethylene carbonate is used instead of versatate.

[0096] Performance testing:

[0097] 1. According to GB201-2000 "Aluminate Cement Standard", the flexural strength and compressive strength of the ferroaluminate cement prepared in Examples 7-9 and Comparative Examples 1-4 were measured.

[0098] 2. An isothermal calorimeter was used to test the total cumulative heat release of the ferroaluminate cement prepared in Examples 7-9 and Comparative Examples 1-4 within 3 days.

[0099] 3. Using a rheometer, the ferroaluminate cements prepared in Examples 7-9 and Comparative Examples 1-4 were poured into the rheometer to test the yield stress and viscosity coefficient of the ferroaluminate cements.

[0100] Table 1: Sample performance test data

[0101] Group Project Example 7 Example 8 Example 9 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Flexural strength / (MPa) 11.2 11.5 12.1 7.8 8.9 9.5 10.2 Compressive strength / (MPa) 73 75 77 51 64 68 70 Cumulative total heat release / (J / g) 182 191 195 178 131 180 175 Yield stress / (Pa) 27 29 31 25 26 16 13 Viscosity coefficient / (Pa·s) 10.3 10.6 11.0 9.8 10.1 8.5 6.7

[0102] Data analysis: By comparing and analyzing the data in Table 1, the ferroaluminate cements prepared in Examples 7-9 of the present invention all have excellent mechanical properties, which are manifested in that the prepared ferroaluminate cements have excellent flexural strength and compressive strength. In Comparative Example 1, when preparing the early strength admixture, 2-methylnaphthalene is used to replace hexadecylnaphthalene with a long fatty chain, so that the dispersibility of the prepared ferroaluminate cement becomes poor and the cement paste is difficult to be uniformly filled, which is manifested in that the flexural strength and compressive strength values ​​of the prepared ferroaluminate cement are significantly reduced.

[0103] The hydration speed of the alumina ferrocement prepared in Examples 7-9 is fast and the reaction degree is high, which is manifested by a large cumulative total heat release value. However, in Comparative Example 2, when preparing the early strength admixture, the early strength admixture is replaced by a long-chain water reducer; the long-chain water reducer improves the retarding effect of the prepared alumina ferrocement by adding triethanolamine; the setting time of the alumina ferrocement prepared in Comparative Example 2 is prolonged, and the cumulative total heat release value becomes smaller. In addition, since calcium lignin sulfonate is not added in the preparation of the early strength admixture, calcium lignin sulfonate has a certain water-reducing effect, which makes the flexural strength and compressive strength values ​​of the alumina ferrocement prepared in Comparative Example 2 decrease.

[0104] In Comparative Example 3, eugenol was used instead of eugenol epoxy resin when preparing the core pre-emulsion and the shell emulsion, so that the core-shell structure failed to form a three-dimensional network cross-linked structure and the coating performance decreased; in Comparative Example 4, ethylene carbonate was used instead of tert-butyl vinyl carbonate when preparing the shell pre-emulsion, thereby reducing the free water content that can be adsorbed in the ferroaluminate cement; the yield stress and viscosity coefficient of the ferroaluminate cement prepared in Comparative Examples 3 and 4 were both reduced.

[0105] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0106] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0107] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A ferroaluminate cement, characterized in that: Calculated by weight, it comprises 75-85 parts of ferroaluminate clinker, 5-10 parts of red mud, 3-5 parts of early strength admixture and 5-10 parts of composite latex powder.

2. A ferroaluminate cement according to claim 1, characterized in that: The preparation method of the early strength admixture comprises the following steps: A1, an organic solvent, sodium aminobenzenesulfonate and hexadecylnaphthalene are mixed, and then a 30-35%wt formaldehyde aqueous solution is added dropwise, and the addition is completed within 1-2 hours; after the addition is completed, a reaction system is obtained; the reaction system is placed in a closed environment and reacted at 90-95°C for 3-4 hours to obtain a long-chain water reducer; A2. Heat water to 80-90°C, mix calcium lignin sulfonate, anhydrous sodium sulfate, triethanolamine, long-chain water reducer, 30%wt sodium hydroxide solution and water, stir evenly to obtain a reactant; heat the reactant to 95-105°C, keep the temperature at this temperature for 2-3 days to obtain an early strength admixture.

3. A ferroaluminate cement according to claim 2, characterized in that: In step A1, the preparation method of the organic solvent is: ethanol and water are mixed in a mass ratio of 2-3:1 to obtain a solution; then NaOH solution is added dropwise to the solution to adjust the pH value of the solution to 8-9 to obtain an organic solvent; the amount ratio of the organic solvent, sodium aminobenzenesulfonate, hexadecylnaphthalene and formaldehyde aqueous solution is 50mL:20-30g:10-15g:50-60mL.

4. A ferroaluminate cement according to claim 2, characterized in that: In step A2, the usage ratio of calcium lignin sulfonate, anhydrous sodium sulfate, triethanolamine, long-chain water reducer, sodium hydroxide solution and water is 3.5-5g:10-15g:0.5-0.8g:5-10g:3-5g:60-65g.

5. A ferroaluminate cement according to claim 1, characterized in that: The preparation method of the composite latex powder comprises the following steps: B1, deionized water, eugenol epoxy resin, N-hydroxyacrylamide and styrene are mixed uniformly to obtain a monomer mixture A; a chain transfer agent and an emulsifier A are added to the monomer mixture A, stirred and dissolved to obtain a core pre-emulsion; B2, deionized water, tert-butyl vinyl carbonate and eugenol epoxy resin are mixed uniformly to obtain a monomer mixture B; emulsifier B is added to the monomer mixture B, and the mixture is mixed and stirred uniformly to obtain a shell pre-emulsion; B3, heating deionized water, ammonium persulfate and part of the core pre-emulsion to 75-80°C, reacting for 15-20 minutes, to obtain an auxiliary agent solution; adding the remaining core pre-emulsion and initiator solution dropwise to the auxiliary agent solution at the same time, adding the core pre-emulsion within 1 hour, adding the initiator solution within 1.5 hours, and keeping the temperature for 0.5-1 hour after the addition is completed, to obtain a core copolymer; B4, adding the shell pre-emulsion and the initiator solution dropwise to the core copolymer at the same time, adding the shell pre-emulsion within 2 hours, and adding the initiator solution within 2.5 hours. After the addition is completed, keep warm for 1-1.5 hours, then cool to 30-40° C., filter, and discharge to obtain a core-shell polymer emulsion; B5. Add the core-shell polymer emulsion and the nano-scale inorganic filler into a spray dryer for spray drying to prepare a composite latex powder.

6. A ferroaluminate cement according to claim 5, characterized in that: In step B1, the chain transfer agent is dodecyl mercaptan, and the emulsifier A is sodium dodecyl diphenyl oxide disulfonate; the amount ratio of the deionized water, eugenol epoxy resin, N-hydroxyacrylamide, styrene, chain transfer agent and emulsifier A is 100mL:30-40g:15-20g:50-100g:4-5g:5-10g.

7. A ferroaluminate cement according to claim 5, characterized in that: In step B2, the emulsifier B is sodium dodecyl diphenyl oxide disulfonate; the amount ratio of the deionized water, tert-butyl vinyl carbonate, eugenol epoxy resin and emulsifier B is 200g:30-50g:20-30g:5-10g; in step B3, 3-5g of ammonium persulfate and 100g of deionized water are mixed to obtain an initiator solution; the amount ratio of deionized water, ammonium persulfate, part of the core pre-emulsion, the remaining core pre-emulsion and the initiator solution is 300g:0.5-1g:10g:190-200g:100g; in step B4, the amount ratio of the core copolymer, the shell pre-emulsion and the initiator solution is 300-400g:200-300g:100g.

8. A ferroaluminate cement according to claim 5, characterized in that: In step B5, the nanoscale inorganic filler is obtained by grinding natural zeolite to 50-100 nm; the mass ratio of the core-shell polymer emulsion to the nanoscale inorganic filler is 90-95:5-10; the inlet temperature of the spray dryer is 170-180°C, and the outlet temperature is 100-105°C.

9. A method for preparing alumina-ferrocement according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Mixing aluminoferrate clinker, red mud, early strength admixture and composite latex powder to obtain a mixture; grinding the mixture to ensure that the residue after passing through an 80 μm sieve is no more than 10-15%wt, and the residue after passing through a 45 μm sieve is no more than 15-20%wt, to obtain a raw material; S2. The raw materials are placed in a curing box at a curing temperature of 20-22° C. and a curing humidity of 90-95% for curing and demolding to obtain demolded cement; the demolded cement is placed in a curing box at a curing temperature of 20-22° C. and a curing humidity of 65-70% for curing for 28 days to obtain ferroaluminate cement.

Citation Information

Patent Citations

  • Iron aluminate cement for repairing and preparation method thereof

    CN115448681A